Multidisciplinary discharge planning: developing a process. - McGinley S; Baus E; Gyza K; Johnson K; Lipton S; Magee MC; Moore F; Wojtyak D (Nursing Management)
In today's health care environment, Frankford Health Care System identified the need for a discharge planning process. A multidisciplinary task force developed and implemented a system that decreased length of stay and duplication of services, improved timeliness of intervention and fostered communication and respect among team members. The process included assessment of patient/family needs and coordination of care, services and referrals for all patients.